The Effect of Discouraged Borrowers on Business Sustainability Through Financial Bootstrapping and Financial Inclusion (Study of Creative Entrepreneurs in Startup Phase) - Dhoni Rizky Widya Mardika; Nur Listiani (KEUNIS, 2026)
This quantitative study aims to examine the effects of discouraged borrowers on financial bootstrapping and financial inclusion, as well as how they affect business performance and business sustainability among startup creative economy entrepreneurs. Data were gathered from innovative MSME participants and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results indicate that the hesitance of business stakeholders to pursue formal funding substantially promotes the use of bootstrapping techniques, while concurrently diminishing the level of financial inclusion. Moreover, both financial bootstrapping and financial inclusion positively influence business performance, thereby enhancing business sustainability. These findings highlight the significance of alternative funding techniques and participation in the formal financial system in encouraging small enterprises’ growth and resilience. Policy implications necessitate enhancing financial bootstrapping, providing management support, and streamlining access to financial services to promote firm autonomy and sustainability.